2020
DOI: 10.1093/tropej/fmaa070
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications of SARS-CoV-2 Infection in Children: A Systematic Review and Meta-Analysis

Abstract: Background Knowledge about neurological complications of COVID-19 in children is limited due to the paucity of data in the existing literature. Some systematic reviews are available describing overall clinical features of COVID-19 in children and neurological complications of COVID-19 in adults. But to the best of our knowledge, no systematic review has been performed to determine neurological manifestations of COVID-19. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
156
2
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(172 citation statements)
references
References 45 publications
(38 reference statements)
6
156
2
8
Order By: Relevance
“…A significant proportion of their parents needed the help of professionals as compared with the parents of children with ADHD. Overall, the need for the help of psychiatric professionals was relatively higher for children with prior behavioral co-morbidities as compared with the general community [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion of their parents needed the help of professionals as compared with the parents of children with ADHD. Overall, the need for the help of psychiatric professionals was relatively higher for children with prior behavioral co-morbidities as compared with the general community [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence has since increased as recent studies have reported rates ranging from 9.4% to 37.7% in neurological patients [ 133 , 134 ]. Interestingly, less than 1% of children reported definite neurological complications such as encephalopathy, seizure, or meningeal signs [ 135 ], indicating that encephalopathy is more common in adult than pediatric COVID-19 patients.…”
Section: Sars-cov-2 Infection Of the Nervous Systemmentioning
confidence: 99%
“…[36][37][38][39][40] The frequency of neurologic involvement in children hospitalized with acute COVID-19 is unclear with 150 of 4190 patients reported across 9 international case series. [41][42][43][44][45][46] Using the Overcoming COVID-19 US public health surveillance registry of children and adolescents hospitalized with COVID-19-related complications, 36 we aimed to describe the type and severity of neurologic involvement and documented hospital outcomes.…”
mentioning
confidence: 99%